Respuesta :

We can use substitution to solve for x then substitute the x value back into the original equation to solve for y...

5x + 2y = 7
y = x + 1

Since y = x + 1, we can substitute x + 1 for y in the first equation

5x + 2(x+1)  = 7
5x + 2x + 2 = 7
7x + 2 = 7
7x = 5
x = 5/7

Now substitute 5/7 for x in either of the original equations

y = x + 1
y = 5/7 + 1
y = 1 5/7

Solution set is (5/7, 1 5/7)

Answer: the solution set would be {(5/7,12/7)}

Step-by-step explanation: had this question on a quiz

ACCESS MORE